Therapeutic targets and signaling mechanisms of dasatinib activity against radiation skin ulcer - Su, Wenxing; Chen, Xuelian; Zhang, Wen; Li, Dazhuang; Chen, Xiaoming; Yu, Daojiang (Frontiers in Public Health, 2022)
Objective: To reveal the potential targets and signaling pathways of dasatinib in the treatment of radiation ulcers through network pharmacology and molecular docking technology. Methods: Pathological targets of radiation ulcers were screened using GeneCards database. At the same time, the pharmacological targets of dasatinib were obtained through SwissTargetPrediction (STP), Binding DB and Drugbank databases. Subsequently, the potential targets of dasatinib for anti-radiation ulcers were obtained after intersection by Venn diagram. Next, a protein-protein interaction (PPI) network was constructed through the STRING database and core targets were screened. Finally, the identified core targets were subjected to GO and KEGG enrichment analysis, co-expression network analysis, and molecular docking technology to verify the reliability of the core targets. Results: A total of 76 potential targets for anti-radiation ulcer with dasatinib were obtained, and 6 core targets were screened, including EGFR, ERBB2, FYN, JAK2, KIT and SRC. These genes were mainly enriched in Adherens junction, EGFR tyrosine kinase inhibitor resistance, Focal adhesion, Bladder cancer and PI3K-Akt signaling pathway. Molecular docking results showed that dasatinib binds well to the core target. Conclusion: Dasatinib may play a role in the treatment of radiation ulcers by regulating EGFR, ERBB2, FYN, JAK2, KIT and SRC. These core targets may provide new insights for follow-up studies of radiation ulcers.